The Comic-strip of Historical Memory: an Analysis of Paracuellos by Carlos Giménez, in the Light of Persépolis by Marjane Satrapi and Maus by Art Spiegelman (Vanderbilt e-Journal of Luso-Hispanic Studies, 2009)
N/A